A computational system to support learning self-regulation to measure knowledge acquisition by students of Computer Science-related courses - Leite, Paula Torales; Silveira, Ismar Frango (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2024)
The evaluation of knowledge acquisition is a constant challenge in the educational field, mainly for learners in higher education – in this paper, students of Computer Sciences-related courses are the main target. In this context, self-regulation and metacognition emerge as tools that might help improve this process, allowing students to monitor their learning process. The objective of this project is to evaluate the applicability of a computational system based on self-regulation for the verification of knowledge acquisition in higher education, in the area of technology. Thereby, we aim to contribute to learners’ learning process and facilitate teachers in keeping up with this evolution. In order to do this, a literary review was conducted, followed by the development of the computational system. The results of the tests conducted with educators indicated a consensus in regard to the viability of the application of the system, highlighting that the proposal contributes to a more humane evaluation and that it helps in the identification of the learners’ needs. In future works, it’s viable to take into consideration points found throughout the research, focusing on the betterment of the system with the aim of applying it effectively in educational environments.